Access to Physical Activity and Sport and the Effects of Isolation and Cordon Sanitaire During COVID-19 for People With Disabilities in Scotland and Canada - Kamyuka, Denise; Carlin, Liz; McPherson, Gayle; Misener, Laura (Frontiers in Sports and Active Living, 2020)
People with a disability (PwD) are more at risk of experiencing inequalities in relation to sporting and physical activity opportunities in addition to accessibility, social and economic inequalities. The challenges posed by Covid-19 may lead to an exacerbation of these experiences and this research directly contributes towards the WHO (2020) global research roadmap priority to explore “the impact of restrictive public health measures (e.g., quarantine, isolation, cordon sanitaire)”. As moderate physical activity decreases risk factors for health conditions such as Type 2 diabetes and CHD (van Schijndel-speet et al. 2014) it is therefore pertinent that groups at a higher risk of these are provided with adequate opportunities to participate. Social loneliness and social isolation have a significant impact on the health and wellbeing of individuals (MacDonald et al, 2017) therefore it is imperative to gain an understanding of the effects of self-isolation and shielding during Covid-19 for people with disabilities to help those in policy and agency positions address these issues. This research utilised an online, qualitative approach, to speak with people with a disability, athletes and non-athletes and those in a position of management and policy making. Five online focus groups, using live captioning, chat functions, and an online written discussion forum; through Project Echo website as part of a wider study on sport and accessibility were utilised. The study also drew on interviews and a focus group with senior policy makers and regional managers responsible for disability sport in Scotland. The paper concludes that People with a Disability have been more isolated, lonely, participated in less physical activity and are at further risk of mental and physical illness due to Covid-19. A collaborative policy approach between governments, governing bodies and key agencies is needed to help participation at recreational level but particularly those in elite sport to train and regain their earnings. Otherwise PwD are at risk of being further excluded from society.